High soybean dietary supplementation with quercetin improves antioxidant capacity of spotted sea bass Lateolabrax maculatus - Longhui Liu; Yanbo Zhao; Zhangfan Huang; Zhongying Long; Huihui Qin; Hao Lin; Sishun Zhou; Lumin Kong; Jianrong Ma; Yi Lin; Zhongbao Li (Aquaculture Reports)
This study aimed to examine the effect of quercetin (QUE) on the antioxidant capacity of spotted sea bass that were fed a high soybean meal diet. 44 % fish meal was used as a healthy control, and soybean meal instead of 50 % fish meal induced a negative reaction. On this basis, 0.25, 0.50, 0.75, and 1.00 g/kg QUE were added, respectively. A total of 540 spotted sea bass were randomly allocated into 6 groups and provided with diets that corresponded to their respective groups for a duration of 56 days. The results showed a significant decrease in the antioxidant capacity of spotted sea bass fed a high soybean meal diet. The inclusion of QUE considerably improved the antioxidant capacity of spotted sea bass. This was evidenced by the notable rise in glutathione (GSH) levels in the intestine and liver, as well as the elevated levels of catalase (CAT) and total antioxidant capacity (T-AOC) in the liver. Furthermore, transcriptome results showed that the S-transferase (GST) gene in the glutathione metabolism pathway was significantly down-regulated by high soybean meal, while with the addition of QUE, noteworthy alterations in genes associated with the PI3K-Akt signaling pathway, Foxo signaling pathway, and AMPK signaling pathway. These signaling pathways are involved in signal transduction, apoptosis, and oxidative stress. On the other hand, genes related to energy metabolism, such as phosphoenolpyruvate carboxykinase (PEPCK), were observed to be upregulated. These pathways could potentially contribute to the antioxidant properties of QUE.